KAJIAN SPASIAL EVALUASI TATA RUANG DAN TATA WILAYAH BERBASIS ZONA KAWASAN RAWAN BENCANA GUNUNG API DI KABUPATEN KARANGASEM PROVINSI BALI - Aji, Adam Hastara; Putro, Dennish Ari (Jurnal Spasial, 2024)
Karangasem Regency Regional Regulation Number 17 of 2012 concerning the RTRW of Karangasem Regency in 2012-2032 is a guide for the Regional Government in preparing the RTRW. This regulation also manages disaster-prone areas (KRB) following the Minister of Energy and Mineral Resources No. 11/2016. In 2017, the Geospatial Information Agency issued a map of the Gunung Agung KRB zone that can be used as a basis for evaluating residential zones that were regulated in the RTRW Regional Regulation. In addition, the conversion of land into a residential zone due to the population growth reached 1980 people/year. This was the reason the existing RTRW needed to be evaluated, given the potential for increased vulnerability due to the emergence of new settlements in the KRB zone. Based on the results of the RTRW evaluation, it was known that residential areas were covering an area of ±566,69 Ha in the KRB II zone and ±160,15 Ha in the KRB III zone which should be a conservation area. Moreover, population growth caused the land conversion of ±992 Ha, where there was an increase in the residential zone in KRB III by ±73,36 Ha which potentially increased the vulnerability of people living in the area.